Transforming the Value of Family Fellowship in Rambu Solo’ Culture: A Christian Education Perspective - Patandung, Yosef; Panggua, Selvi; Sukito, Adi; Randalele, Christian Elyesar (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2025)
Rambu Solo’, a traditional Torajan funeral ceremony, embodies strong values of family fellowship that continue to be practiced within predominantly Christian communities in North Toraja. However, the transformation of these cultural values into Christian Religious Education (CRE) has not been systematically explored. This study aims to examine how the family fellowship values embedded in the cultural context of Rambu Solo’ are transformed into the values of Christian Religious Education.This study employed a qualitative ethnographic approach and was conducted in North Toraja Regency. Data were collected through in-depth interviews with two key informants, a traditional leader who also serves as a pastor and a Christian Religious Education teacher, as well as through participant observation during Rambu Solo’ ceremonies. The data were analyzed using thematic content analysis and theological-hermeneutical reflection. Ethical considerations were ensured through informed consent, voluntary participation, and the confidentiality of informants.The findings revealed two core values of family fellowship within Rambu Solo’: (1) unity in thought and emotion (sangngina and karapasan), and (2) unity in action through mutual cooperation (sangtiangkaran). These values are culturally preserved while being theologically reinterpreted within Christian education. The transformation process demonstrates that the cultural values of unity and mutual assistance are not eliminated; rather, they are reoriented toward biblical principles of fellowship, particularly the unity of believers in Christ and communal responsibility within the Body of Christ. Therefore, Rambu Solo’ functions as a cultural medium through which Christian Religious Education contextualizes biblical teachings on unity, love, and communal solidarity within Toraja society.